2018
DOI: 10.1021/jacs.8b02319
|View full text |Cite
|
Sign up to set email alerts
|

Electroenzymatic C–C Bond Formation from CO2

Abstract: Over the past decade, there has been significant research in electrochemical reduction of CO, but it has been difficult to develop catalysts capable of C-C bond formation. Here, we report bioelectrocatalysis of vanadium nitrogenase from Azotobacter vinelandii, where cobaltocenium derivatives transfer electrons to the catalytic VFe protein, independent of ATP-hydrolysis. In this bioelectrochemical system, CO is reduced to ethylene (CH) and propene (CH), by a single metalloenzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 31 publications
(34 reference statements)
1
78
0
Order By: Relevance
“…Furthermore, N 2 fixation with artificial systems is still in its infancy and pertinent mechanistic questions can extracted from studies with semi-artificial enzyme-hybrids. Of further interest is also the continued exploration of the promiscuity of N 2 ases, which exhibit activity towards H 2 production 86 , CO 2 reduction to C 1 products 87 and even C-C coupling 88 .…”
Section: Photoreductive Reactionsmentioning
confidence: 99%
“…Furthermore, N 2 fixation with artificial systems is still in its infancy and pertinent mechanistic questions can extracted from studies with semi-artificial enzyme-hybrids. Of further interest is also the continued exploration of the promiscuity of N 2 ases, which exhibit activity towards H 2 production 86 , CO 2 reduction to C 1 products 87 and even C-C coupling 88 .…”
Section: Photoreductive Reactionsmentioning
confidence: 99%
“…Supporting density functional theory (DFT) calculations led to the conclusion that the protonation of a M-H at the FeMo-co is the rate-limiting step of H 2 evolution (within the MoFe protein component). In 2018, Cai et al also employed this approach to investigate catalysis of the VFe protein for H + and CO 2 reduction [171]. In addition to unsubstituted cobaltocene, mono-cobaltocene ([Co(Cp)(CpCOOH)], E o ' = −0.79 V vs. SHE) and di-carboxy cobaltocene ([Co(CpCOOH) 2 ], E o ' = −0.65 V vs. SHE) derivatives were also investigated as electron mediators for the VFe protein.…”
Section: Electrochemical Methods For Electron Transfermentioning
confidence: 99%
“…Cobaltocene‐mediated electrocatalysis was subsequently adopted to facilitate H + and CO 2 reduction by MoFe and the alternative FeFe protein (producing H 2 as well as HCOO − ) . Further, cobaltocene‐mediated electrocatalysis with the alternative VFe protein (where two additional cobaltocene derivatives were also explored) demonstrated that C−C bond formation could be catalyzed forming ethene and propene from CO 2 reduction . When coupled with its Fe protein (and ATP hydrolysis), the VFe protein is known to catalyze C−C bond formation from CO reduction …”
Section: Recent Examples Of Enzymatic Electrochemistry For Small Molementioning
confidence: 99%